Coronary Artery Spasm: New Insights - Anthony Matta; Frederic Bouisset; Thibault Lhermusier; Fran Campelo-Parada; Meyer Elbaz; Didier Carrié; Jerome Roncalli (Journal of Interventional Cardiology)
Coronary artery spasm (CAS) defined by a severe reversible diffuse or focal vasoconstriction is the most common diagnosis among INOCA (ischemia with no obstructive coronary artery disease) patients irrespective to racial, genetic, and geographic variations. However, the prevalence of CAS tends to decrease in correlation with the increasing use of medicines such as calcium channel blockers, angiotensin converting enzyme inhibitor, and statins, the controlling management of atherosclerotic risk factors, and the decreased habitude to perform a functional reactivity test in highly active cardiac catheterization centers. A wide spectrum of clinical manifestations from silent disease to sudden cardiac death was attributed to this complex entity with unclear pathophysiology. Multiple mechanisms such as the autonomic nervous system, endothelial dysfunction, chronic inflammation, oxidative stress, and smooth muscle hypercontractility are involved. Regardless of the limited benefits proffered by the newly emerged cardiac imaging modalities, the provocative test remains the cornerstone diagnostic tool for CAS. It allows to reproduce CAS and to evaluate reactivity to nitrates. Different invasive and noninvasive therapeutic approaches are approved for the management of CAS. Long-acting nondihydropyridine calcium channel blockers are recommended for first line therapy. Invasive strategies such as PCI (percutaneous coronary intervention) and CABG (coronary artery bypass graft) have shown benefits in CAS with significant atherosclerotic lesions. Combination therapies are proposed for refractory cases.